GADOTTI, Moacir. Concepção dialética da educação: um estudo introdutório. 16. ed. São Paulo: Cortez, 2018. 208p. - Rodrigues, Stélio João (Vox Scripturae - Revista Teológica Internacional, 2018)
GADOTTI, Moacir. Concepção dialética da educação: um estudo introdutório. 16. ed. São Paulo: Cortez, 2018. 208p.